Peroneal tendon pathology: Pre- and post-operative high resolution US and MR imaging. Issue 92 (July 2017) - Kumar, Yogesh; Alian, Ali; Ahlawat, Shivani; Wukich, Dane K.; Chhabra, Avneesh
Highlights: Peroneal brevis split tear should be distinguished from bifid/accessory tendons. Painful os peroneum syndrome is 2nd most common cause of lateral hindfoot pain. Incompetent superior peroneal retinaculum and tendon adhesions can be confirmed with US or MR kinematic imaging. Thickening, increased T2 signal and arrowhead shape of peroneal brevis are normal post-operative findings. MRI provides comprehensive ankle evaluation in post-operative failure cases. Abstract: Peroneal tendon pathology is an important cause of lateral ankle pain and instability. Typical peroneal tendon disorders include tendinitis, tenosynovitis, partial and full thickness tendon tears, peroneal retinacular injuries, and tendon subluxations and dislocations. Surgery is usually indicated when conservative treatment fails. Familiarity with the peroneal tendon surgeries and expected postoperative imaging findings is essential for accurate assessment and to avoid diagnostic pitfalls. Cross-sectional imaging, especially ultrasound and MRI provide accurate pre-operative and post-operative evaluation of the peroneal tendon pathology. In this review article, the normal anatomy, clinical presentation, imaging features, pitfalls and commonly performed surgical treatments for peroneal tendon abnormalities will be reviewed. The role of dynamic ultrasound and kinematic MRI for the evaluation of peroneal tendons will be discussed. Normal and abnormal postsurgical imaging appearances will be illustrated.